Improving functionality of myofibrillar protein: A comparative study on fat types on the resulting gelling and microstructure properties - Nurul Shaeera Sulaiman; Hana Mohd Zaini; Md Jahurul Haque Akanda; Man Hin Heong; Anthony Chai; Wolyna Pindi (Springer nature link, 2024)
Myofibrillar proteins are mainly responsible for the structure-forming properties of emulsified meat products due to their gelling abilities. To enhance the gel characteristics of myofibrillar protein, the effect of lipids in different physical states on MP gelation was studied. In this study, chicken fat (CF), refined palm oil (RPO), and palm stearin (ST) were used to emulsify the extracted chicken myofibrillar protein (MP). The whiteness, water holding capacity, gel strength, solubility, emulsifying stability index, thermal and rheological properties, protein separation, and microstructure of MP gels were evaluated. The results demonstrated that RPO addition increased the physicochemical parameters, followed by CF and ST, and the ratio between MP and lipid was 4 to 1. MP-RPO also showed better thermal properties, characterized by a high peak temperature of peak 3 during differential scanning calorimetry analysis. MP-ST was the most unstable, indicated by the lowest peak temperature, while MP-CF did not differ significantly from MP-RPO. The frequency sweep test showed that RPO has the highest G’ and lowest tan δ values, indicating a strong network formation. The changes in electrophoresis bands demonstrated that myosin might be involved in creating heat-induced MP gel, with no difference between lipid types. Additionally, the microstructure showed that MP-RPO gel had smaller oil droplets coated with interfacial protein film. Hence, RPO might be the best lipid source when emulsifying chicken protein due to its high water holding capacity with excellent thermal and rheological properties.